THE LEVEL OF PRINCIPAL’S INSTRUCTIONAL LEADERSHIP PRACTICES AND ITS RELATIONSHIP WITH SCHOOL-BASED MANAGEMENT IN SECONDARY SCHOOL IN TUMPAT DISTRICT, KELANTAN, MALAYSIA - Goh Chong Ping; Mohd Izham Mohd Hamzah (International Journal of Educational Best Practices, 2021)
This study aims to identify the level of principals’ instructional leadership practices and their relationship with the school-based management in secondary schools in Tumpat district, Kelantan. This study was conducted in the form of survey using a quantitative method with a total of 286 respondents using a questionnaire as a research instrument. Quantitative data were analyzed descriptively and inferentially using SPSS software version 25.0. The result of this study showed that the level of principal's instructional leadership practices was high (mean=4.25, s.d.=0.444) where the dimension of forming a positive school environment scored the highest mean (mean=4.30, s.d.=0.459). The level of school-based management was also high (mean=4.24, s.d.=0.427) with the highest score mean dimension was the dimension of planning and evaluation (mean=4.29, s.d.=0.450). The Pearson correlation test showed a significant relationship between the level of principals’ instructional leadership practices and school-based management which was at a high correlation level (r=0.895). Therefore, the implication of this study is able to provide an exposure to the Ministry of Education Malaysia who can take initiatives to make improvements in the basic aspects of education and also leadership programs in order to strengthen the leadership practices of principals in schools. This study also has implications to school principals in re-evaluating all their practices and actions in managing schools to further improve the effectiveness and the quality of their administration. In conclusion, this study gives the impression that principals’ instructional leadership practices have impacts on school-based management which to some extent can affect the performance of teachers and students as well as the results of the effectiveness of school functions.